Micro- and nanoscale fluid mechanics : transport in microfluidic devices - Kirby, Brian J. (Brian James), 1973- (New York : Cambridge University Press, 2010)
"Intended for graduate and undergraduate students and as a reference for practicing researchers, this text focuses on the physics of fluid transport in micro- and nanofabricated systems"--Provided by publisher.
"This text focuses on the physics of fluid transport in micro- and nanofabricated liquid-phase systems, with consideration of gas bubbles, solid particles, and macromolecules. This text was designed with the goal of bringing together several areas that are often taught separately - namely, fluid mechanics, electrodynamics, and interfacial chemistry and electrochemistry - with a focused goal of preparing the modern microfluidics researcher to analyze and model continuum fluid mechanical systems encountered when working with micro- and nanofabricated devices. This text is not a summary of current research in the field, and it omits any discussion of microfabrication techniques or any attempt to summarize the technological state of the art. This text serves as a useful reference for practicing researchers but is designed primarily for classroom instruction. Worked sample problems are inserted throughout to assist the student, and exercises are included at the end of each chapter to facilitate use in classes"--Provided by publisher.
Machine generated contents note: 1. Kinematics, conservation equations, and boundary conditions for incompressible flow; 2. Unidirectional flow; 3. Hydraulic circuit analysis; 4. Passive scalar transport: dispersion, patterning, and mixing, 5. Electrostatics and electrodynamics; 6. Electroosmosis; 7. Potential fluid flow; 8. Stikes flow; 9. The diffuse structure of the electrical double layer; 10. Zeta potential in microchannels; 11. Species and charge transport; 12. Microchip chemical separations; 13. Particle electrophoresis; 14. DNA transport and analysis; 15. Nanofluidics: fluid and current flow in molecular-scale and thick-double-layer systems; 16. AC electrokinetics and the dynamics of diffuse charge; 17. Particle and droplet actuation: dielectrophoresis, magnetophoresis, and digital microfluidics; A. Units and fundamental constants; B. Properties of electrolyte solutions; C. Coordinate systems and vector calculus; D. Governing equation reference; E. Nondimensionalization and characteristic parameters; F. Multipolar solutions to the Laplace and Stokes equations; G. Complex functions; H. Interaction potentials: atomistic modeling of solvents and solutes.
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Microfluidic devices; Microfluidics; Nanofluids